2014
DOI: 10.1186/1476-511x-13-193
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids furom Coreopsis tinctoria adjust lipid metabolism in hyperlipidemia animals by down-regulating adipose differentiation-related protein

Abstract: BackgroundTo identify the chemical structure of Coreopsis tinctoria extracts and their effect and mechanism on reducing blood lipid in hyperlipemia mice.MethodsThe flavonoids were extracted from Coreopsis tinctoria. The chemical structure was identified by HPLC. 59 mice were divided randomly into 5 groups. (group 1: normal diet control; group 2: hyperlipemia model; group 3: hyperlipemia mice treated with Coreopsis tinctoria, low dose 100 mg/kg; group 4: hyperlipemia mice treated with Coreopsis tinctoria high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…C. tinctoria is an ornamental plant widely cultivated in China and in many other counties, such as Canada, Mexico and the United States. It has been reported that C. tinctoria possesses many biological activities, including anti-inflammatory, antioxidant, anti-hyperlipidemic and anti-hypoglycemic activities [156,157]. Its anti-inflammatory activity has been mainly attributed to inhibition of COX-2 expression [158].…”
Section: Plant-derived Metabolitesmentioning
confidence: 99%
“…C. tinctoria is an ornamental plant widely cultivated in China and in many other counties, such as Canada, Mexico and the United States. It has been reported that C. tinctoria possesses many biological activities, including anti-inflammatory, antioxidant, anti-hyperlipidemic and anti-hypoglycemic activities [156,157]. Its anti-inflammatory activity has been mainly attributed to inhibition of COX-2 expression [158].…”
Section: Plant-derived Metabolitesmentioning
confidence: 99%
“…In our previous research using an animal model, we found the active flavonoid compounds from CT extracts have anti-hyperlipidemia effects, particularly in lowering triglycerides, reducing lipid deposition, and protecting liver function [9]. Reductions in LDL can decrease major cardiovascular events in clinical trials [31,32]; thus, reducing LDL cholesterol has been incorporated into practice guidelines as a fundamental means of reducing cardiovascular morbidity and mortality [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The mouse model of hyperlipidemia was generated by oral feeding of a high-fat diet (20% lard, 10% cholesterol, 2% bile salts, 0.2% propylthiouracil, 20% propylene glycol, 20% polysorbate-80; 0.2 mg/per 10 g weight per day) for 2 weeks [9]. The hyperlipidemia model was confirmed by blood lipid tests after continuous feeding for 2 weeks.…”
Section: Establishment and Study Of A Mouse Model Of Hyperlipidemiamentioning
confidence: 99%
See 2 more Smart Citations